More than two decades of gastrodiplomacy: a review of the concept, current characteristics, and future trends - Li, Guofeng; Mok, Kakio (Frontiers in Political Science, 2025)
This article presents a scoping review of 64 publications on gastrodiplomacy, a growing subfield within diplomatic studies that explores the strategic use of national cuisine as a tool for public and cultural diplomacy. Building on foundational literature and recent empirical studies, the review maps the conceptual, methodological, and thematic developments of gastrodiplomacy research over the past two decades. The analysis reveals a growing scholarly consensus around the field’s core elements—strategic objectives, operative agents, and mechanisms of influence—while also highlighting a strong geographic and economic bias toward developing countries in Asia. Although most existing studies emphasize national-level campaigns led by state actors, an emerging body of work now focuses on sub-state and non-state actors such as diaspora communities, chefs, and influencers. The study identifies three future research directions: methodological diversification through primary data and micro-level analysis; expanded geographic scope beyond Asia and small/middle powers; and the incorporation of critical perspectives. By offering a comprehensive review focused exclusively on the concept of gastrodiplomacy, this article contributes to the consolidation of the field and provides a foundation for further theoretical, comparative and impact-based research.